Genome-Wide Association Study to Characterize Serum Bilirubin Elevations in Patients with HCV Treated with Gs-9256, An HCV Ns3 Serine Protease Inhibitor. Issue 7 (October 2014) - Nelson, David; Yoshida, Eric M; Paulson, Matthew S; Hengen, Paul N; Ge, Dongliang; Kanwar, Bittoo; McNally, John; Pang, Phillip S; Subramanian, G Mani; McHutchison, John G; Urbanek, Petr; Lawitz, Eric; et al.
Background: Protease inhibitors for the treatment of HCV can cause mild and reversible elevations of unconjugated bilirubin. We sought to characterize genetic determinants of bilirubin elevations using a genome-wide approach among patients with genotype 1 HCV who received combination therapy that included GS-9256, a novel potent inhibitor of HCV NS3 serine protease, as part of a Phase IIb trial. Methods: Of the 200 patients sampled, 176 had confirmed European ancestry and were included in the analysis. Infinium HumanOmni5BeadChip (Illumina, Inc., San Diego, CA, USA) was used for genotyping. A categorical analysis of low (grade 0–1) versus high (grade 2–4) bilirubin toxicity grade and a quantitative trait locus mapping of peak bilirubin concentrations was performed. Results: A total of 4, 466, 809 genetic markers were analysed. No single variant showed a statistically significant association with observed bilirubin elevations in this patient population. In a targeted analysis of single nucleotide polymorphisms in genes known to be involved in bilirubin transport, no significant differences in allele frequency between high and low bilirubin toxicity grade were observed. Conclusions: These results indicate that risk for bilirubin elevation in patients receiving GS-9256 is unlikely to be strongly influenced by common genetic variants with large effects. The current study cannot rule out a role for common variants of weak effect, or a more complex model, including multiple contributing factors, such as rare variants and as yet unidentified environmental influences.